2000
DOI: 10.1016/s0735-1097(00)00997-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile and long-term follow-up of 37 families with arrhythmogenic right ventricular cardiomyopathy

Abstract: Arrhythmogenic right ventricular cardiomyopathy is a progressive disease appearing during adolescence and early adulthood. Systematic evaluation of family members leads to early identification of ARVC, characterized by a broad clinical spectrum with a favorable outcome. In the setting of positive family history, even minor ECG and echocardiographic abnormalities are diagnostic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
265
0
6

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 404 publications
(288 citation statements)
references
References 35 publications
17
265
0
6
Order By: Relevance
“…When these modified criteria are used to screen relatives, 39% of them will have signs of the disease, as opposed to 28% if the original criteria were used 36 . A similar percentage (41%) was reported by Nava et al 37 . During a long-term follow-up (mean 8.5 years) of 37 Italian families encompassing 365 subjects, Nava et al…”
Section: Evaluation Of Relativessupporting
confidence: 89%
See 1 more Smart Citation
“…When these modified criteria are used to screen relatives, 39% of them will have signs of the disease, as opposed to 28% if the original criteria were used 36 . A similar percentage (41%) was reported by Nava et al 37 . During a long-term follow-up (mean 8.5 years) of 37 Italian families encompassing 365 subjects, Nava et al…”
Section: Evaluation Of Relativessupporting
confidence: 89%
“…reported a favorable prognosis even for affected patients (mortality rate of 0.08 patients/year) 37 . Despite this fact, diligent medical care of these patients is of utmost importance and they should avoid strenuous physical activity.…”
Section: Evaluation Of Relativesmentioning
confidence: 99%
“…8,9 Higher numbers, however, are found in specific regions, for example, the Veneto region of Italy. 10 …”
Section: Mutational Spectrummentioning
confidence: 99%
“…5,13,17,18 Index case in that family had not been tested: ARVC is believed to be familial in B30-50% of cases. 1,8,9,20 Therefore, when an index patient has been clinically diagnosed with ARVC, and no genetic test has been performed, the chance for a firstdegree relative to develop ARVC may reach up to 15-25%.…”
Section: Positive Clinical Predictive Valuementioning
confidence: 99%
“…However, long-term favourable course of the disease has also been described. The mortality rate in published studies is shown in Table 1 (7,8,(28)(29)(30)(31)(32)(33). Recently, Hulot et al (31), described the natural history of 130 patients with ARVC/D who were referred to a tertiary center and followed for 8.1±7.8 years.…”
Section: Natural History and Mortalitymentioning
confidence: 99%